The global neonatal and pediatric sepsis initiative - Kissoon, Niranjan; Carcillo, Joseph A. (Journal of Pediatric Infectious Diseases, 2009)
Sepsis and septic shock are major contributors to mortality in children worldwide. While many factors may contribute to poor outcomes, resource limitations play a role in developing countries. However, early recognition and aggressive therapy using simple measures can reverse shock in most children. Indeed great gains have been realized in some areas with limited resources. In this manuscript, we outline the treatment of sepsis in children based on the resources available in various countries. This approach forms the basis of the World Federation of Pediatric Intensive and Critical Care Societies sepsis initiatives. An invitation is extended to participate in this global sepsis initiative.
Keywords: Sepsis; septic shock; children; treatment; outcome